Invasive Meningococcal Disease on the Workplaces: a systematic review - Riccò, Matteo; Vezzosi, Luigi; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2017)
Background and aims of the work: Invasive Meningococcal Disease (IMD) represents a global health threat, and occupational settings have the potential to contribute to its spreading. Therefore, here we present the available evidences on the epidemiology of IMD on the workplaces. Methods: The following key words were used to explore PubMed: Neisseria meningitidis, meningococcus, meningococcal, invasive meningococcal disease, epidemiology, outbreaks, profession(al), occupation(al). Results: We identified a total of 12 IMD cases among healthcare workers (HCW), 44 involving biological laboratory workers (BLW), 8 among school personnel, and eventually 27 from other settings, including 3 large industrial working populations. Eventual prognosis of BLW, particularly the case/fatality ratio, was dismal. As clustered in time and space, data about school cases as well as industrial cases seem to reflect community rather than occupational outbreaks. In general, we identified a common pattern for HCW and BLW, i.e. the exposure to droplets or aerosol containing N meningitidis in absence of appropriate personal protective equipment (PPE) and/or microbiological safety devices (MSD) (e.g. cabinets). Post-exposure chemoprophylaxis (PEC) was rarely reported by HCW (16.7%) workers, and never by BLW. Data regarding vaccination status were available only for a case, who had failed requested boosters. Conclusions: The risk for occupational transmission of IMD appears relatively low, possibly as a consequence of significant reporting bias, with the exception of HCW and BLW. Improved preventive measures should be implemented in these occupational groups, in order to improve the strict use of PPE and MSD, and the appropriate implementation of PEC.